Development of STEM E-Book Integrated with Religion Values in IPAS Subject - Deprizon; Berry Kurnia Vilmala; Refika (Postgraduate, University of Mataram, 2025)
Education plays an important role in shaping the character and progress of a country. Technological developments should be used to make innovations in achieving educational goals. One of them is to use electronic books because of the flexibility of learning, interactivity, ease of searching, and ease of updating. The use of E-Books in digital education courses is highly correlated with the learning objectives of digital education courses, one of which is to develop skills in using various digital tools and platforms to support the learning and teaching process. PGMI students are expected to compete with current technological developments while maintaining the goals of national education, namely forming students who have faith and piety in God Almighty. This research type of research and development (R&D) uses the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This research aims to create a STEM E-Book integrated with religious values in thematic courses (IPAS). In the validation level, the Learning media expert validator obtained a score of 94.16% with the category